Mechanism of Antibiotic TC Degradation by H₂O₂ - Paril, Paolo; Santangelo, Tala; Carr, Bela (Journal of Green Energy and Environmental Engineering, 2024)
The mechanism by which EDTA-Fe⁰ catalyzes hydrogen peroxide (H₂O₂) to degrade pollutants remains unclear in alkaline-catalyzed H₂O₂ systems. This study selected EDTA-Fe⁰ as the catalyst and tetracycline (TC) as the target pollutant to investigate the degradation behavior and mechanism of the H₂O₂ system. The results demonstrated that the EDTA-FE⁰/H₂O₂ system achieved 90.2% TC removal within 60 minutes under neutral conditions, whereas the unmodified FE⁰/H₂O₂ system only removed 23.9% of TC. This modified FE⁰ broadened the pH limitations of Fenton-like reactions. The EDTA-FE⁰/H₂O₂ system not only applied to various pollutants but also exhibited excellent recyclability, adaptability to natural substances, and effective performance in treating real wastewater. Using SEM, FTIR, XPS, WCA measurements, we confirmed the mechanisms by which EDTA-Fe⁰ efficiently catalyzed H₂O₂. Additionally, it was detected Fe–OH, Fe–OOH, and Fe–O peaks in both Fe⁰ hydrogen peroxide and EDTA-Fe⁰ hydrogen peroxide systems, proving that hydrogen peroxide decomposition follows two distinct pathways.